2021
DOI: 10.1186/s12884-021-03848-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and determinants of neural tube defect in Africa: a systematic review and meta-analysis

Abstract: Background Neural tube defects (NTDs) are a group of disorders that arise from the failure of the neural tube close between 21 and 28 days after conception. About 90% of neural tube defects and 95% of death due to these defects occurs in low-income countries. Since these NTDs cause considerable morbidity and mortality, this study aimed to determine the prevalence and associated factors of NTDs in Africa. Methods The protocol of this study was regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 62 publications
1
10
1
4
Order By: Relevance
“…NTDs represent a substantial health burden in Ethiopia [8], [13], [14]. A systematic meta-analysis from different countries in Africa revealed a pooled birth prevalence of 21 per 10,000 births in Africa and suggested that Ethiopia was one of the countries with highest prevalence of NTD in Africa [15]. In contrast, a systematic review of data from 75 countries with different health system and economic developmental levels found a median prevalence of NTD at birth of 1.1 per 10,000 births [6].…”
Section: Discussionmentioning
confidence: 99%
“…NTDs represent a substantial health burden in Ethiopia [8], [13], [14]. A systematic meta-analysis from different countries in Africa revealed a pooled birth prevalence of 21 per 10,000 births in Africa and suggested that Ethiopia was one of the countries with highest prevalence of NTD in Africa [15]. In contrast, a systematic review of data from 75 countries with different health system and economic developmental levels found a median prevalence of NTD at birth of 1.1 per 10,000 births [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis study that included 19 studies from 1968 to 2013, the overall pooled prevalence of NTDs in India was 45.00 per 10,000 total births (95% CI 42.00, 49.00) [ 28 ]. In a recent study, which included a meta-analysis of 37 publications from the African region in 1990 and 2020, the prevalence of NTDs was reported as 50.71 (95% CI 48.03, 53.44) per 10,000 births [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…), genetic predisposition, and environmental factors play a role in the etiology [ 2 , 7 9 ]. Geography, race, maternal obesity, antiepileptic drug use, pesticide exposure, smoking, indoor air pollution from predominantly biomass heating, x-ray radiation exposure, family history, and previous history of stillbirth have been reported to contribute to the development of NTDs [ 10 13 ]. Previous studies have shown that a significant proportion of NTDs can be prevented with pre-pregnancy folic acid supplementation (PFAS) [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the negative medical side effects caused by an enhanced and indiscriminate use of pesticides ( 69 , 70 ). Several lines of evidence reported that pesticides contribute to significant developmental and reproductive disorders with carcinogenic and teratogenic capabilities ( 69 , 71 , 72 ). Several previous experimental and case reports indicated a connection between congenital disorders and pesticide exposure ( 69 71 , 73 , 74 ).…”
Section: Etiology—neural Tube Defectsmentioning
confidence: 99%